ANALISIS PERMASALAHAN DALAM PEMBELAJARAN IPA DI KELAS V SDN 1 CEMPAGA - Darmayanti, NWS; Widiani, N Wayan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Low science learning outcomes are caused by internal student factors, which include interests, talents, study habits and external factors of students such as school environment, family, community, and learning facilities and infrastructure. The purpose of this study is to analyze problems in science learning in grade V SDN 1 Cempaga. This research uses a descriptive method with a qualitative approach. Data collection techniques are carried out by interviews and observations, then the data is described in the form of words or sentences that have certain meanings. The data collection process was carried out in October 2023 with the subjects of this study being a class teacher and 32 grade V students of SDN 1 Cempaga. Next, the data was analyzed descriptively qualitatively. From the results of data analysis, it shows that there is still low interest and motivation of students in learning, which is characterized by a lack of student activity. Furthermore, teachers need to increase student motivation by using interesting and varied methods to encourage activeness and student involvement in learning.